An exploration of the reception and expectations of medical information among hospitalized elderly patients and their primary caregivers in Taiwan: a mixed-methods study - Chen, Kai-Li; Chang, Chia-Ming; Huang, Mei-Chih; Chen, Ching-Huey (Jurnal Ners, 2023)
Objectives Adults older are increasing in Taiwan. The receipt of information and expectations related to informational messages provided to hospitalized elders have not been studied. The study aim is to explore the status of receipt of information and expectations among hospitalized elders and their care providers in Taiwan. Methods A descriptive, cross-sectional and mixed-methods study design was used in in a geriatric ward in a medical center. The participants were 60 patients of 65 years and their care providers were obtained by convenience sampling. The data were collected using a semi-structured questionnaire and checklists. Physician messages and the data for each participant were collected in one regular ward round. Results Twenty-eight patients (46.7%) could not repeat the messages. The message repetition rate was 21.9% the first hour and was 62.9% after hinting. The total message repetition rate of the main care providers was 36.0% and was 80.3% after hinting. "Desire to know the reasons for discomfort” and "discharge date” were the messages most expected by the patients. "None,” "conditions associated with the progress of the illness,” "discharge date” and "relevant information of examination results” were the messages most expected by their care providers. Conclusions The majority of the hospitalized elderly and their care providers could not repeat medical messages conveyed by the physicians. The informed messages should be sorting, and the reminder should be repeated within a short time.  Keywords: receipt of information, expectation, hospitalized elders, care providers, Taiwan.